Cancer Risk in Individuals With Major Birth Defects: Large Nordic Population Based Case-Control Study Among Children, Adolescents, and Adults. Issue 4 (April 2021) - Daltveit, Dagrun Slettebø; Klungsøyr, Kari; Engeland, Anders; Ekbom, Anders; Gissler, Mika; Glimelius, Ingrid; Grotmol, Tom; Madanat-Harjuoja, Laura; Ording, Anne Gulbech; Sæther, Solbjørg Makalani Myrtveit; Sørensen, Henrik Toft; Troisi, Rebecca; et al.
Abstract : (Abstracted from BMJ 2020;371:m4060) Birth defects are strong risk factors for childhood cancers. While past studies have identified associations between birth defects and cancer in children, few have looked at these associations into adulthood.